Developing Model and Psychological Competencies Scale of 100 Meter Runner Student Athletes - Rachman Widohardhono; Nurhasan Nurhasan; Edy Mintarto; Miftakhul Jannah (IJORER : International Journal of Recent Educational Research, 2022)
The main aim of research is to develop model and instrument psychological competencies scale (PCS) of 100 Meter Student Athletes. This research use a mixed methods approach. 1st Study, used a qualitative approach, identifying the constructs and dimensions of elite 100 meter runner student athletes. Using literature review and interview of 2 elite athletes and 2 coaches. The results of the first study is psychological competencies model consists of goal setting, goal setting, motivation, concentration, emotion regulation, focus, self talk, self confidence, and persistence. Another result is 10 items of multidimentional measure of PCS. Each items in the scale were responded on five point level. Leveling describes psychological abilities based on behavior. 2nd Study, using a quantitative approach, instrument validation and reliability testing. We recruited 50, age 18-22 years from 100 meters runner student athletes voluntarily participated in this study. We assessed construct validity by examining how well the measures discriminated groups expected to differ based on their competencies, using Corrected Item-Total Correlation with a minimum limit of 0.300 to be declared a valid item. We assessed internal consistency of PCS using the Cronbach Alpha coefficient. The result of Corrected Item-Total Correlation obtained results All items are valid because they have a Corrected Item-Total Correlation value greater than the minimum limit of 0.300. The internal consistency of the (Cronbach’s alpha coefficient) was 0.841. It can be concluded that PCS is valid and reliable for measuring for 100 meter runner student athlete.